2009
DOI: 10.1021/jf900285e
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Study of the Complexation of Pterostilbene by Natural and Modified Cyclodextrins

Abstract: In this paper, the interaction between pterostilbene and cyclodextrins (CDs) is described for the first time using steady-state fluorescence. It was seen that pterostilbene forms a 1:1 complex with all of the natural (alpha-, beta-, and gamma-CDs) and modified (HP-beta-CD, methyl-beta-CD, and ethyl-beta-CD) CDs tested. Among natural CDs, the interaction of pterostilbene with beta-CD was the most efficient. However, all of the modified CDs showed higher complexation constants (K(F)) than beta-CD. The highest K(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
4
34
2
Order By: Relevance
“…The fact that ␤-CD was the optimum natural CD for complexing oxyresveratrol is in good agreement with the results of most of papers which compare the complexation of several stilbenoids compounds with natural CDs [7][8][9][10][11].…”
Section: Effect Of the Cyclodextrin Structure On The Complexation Of supporting
confidence: 89%
See 3 more Smart Citations
“…The fact that ␤-CD was the optimum natural CD for complexing oxyresveratrol is in good agreement with the results of most of papers which compare the complexation of several stilbenoids compounds with natural CDs [7][8][9][10][11].…”
Section: Effect Of the Cyclodextrin Structure On The Complexation Of supporting
confidence: 89%
“…Although several authors have claimed that stilbenes can not form CD complexes with a 1:2 stoichiometry, López-Nicolás et al [10] demonstrated that trans-stilbene can able to be complexed by two molecules of HP-␤-CD. For this reason, we studied the possible formation of a 1:2 oxyresveratrol/␤-CD complex via a pre- cursor 1:1 complex (Fig.…”
Section: Mechanism Of Complexation Of Oxyresveratrol Byˇ-cdmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, we can note, that the stability constant for LU-HPbCD and LU-DMbCD complexes decrease with increasing temperature as expected for an exothermic process, which might be interpreted as a lower degree of interaction at higher temperatures, possibly due to the fact that hydrogen bonds are usually weakened by heating. 23 However, for LU-bCD, stability constant increase as temperature rises, as expected for an endothermic process. These temperature effects on the association constant were also found for galangin-cyclodextrin complexes.…”
Section: Resultsmentioning
confidence: 88%